Pengaruh Media Loosepart Terhadap Perkembangan Kognitif Anak Usia Dini. Penelitian di Kelas A Kelompok Bermain Hidayatul Islah - Paridah Hidayat; Ina Haerina (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to know the use of loosepart media in class A of Hidayatul Islaht’s kindergarten,to know cognitive development in class A of Hidayatul Islah’s kindergarten, and to find out the influence of loosepart media on cognitive development in class A of Hidayatul Islah’s kindergarten. This type of research is quantitave research. The research subject are student. The data collection techniques used in this research are observation, interview and documentation. Data processing techniques using the SPSS 24 application and analysis using annova test. Based on the result of data processing, this research shows that the use of loosepart media  is in the 50% it means pretty good, and cognitive development is in 45%,  it means pretty good too. This indicates that there is an influenceof loosepart media on cognitive development in class A of Hidayatul Islah’s Kindergarten.